Treści kulturowe w dawnych polskich podręcznikach do nauki języka angielskiego (1788–1950) - Kotlarska, Irmina (Neofilolog, 2023)
The article describes the glottodidactic aspects of the relationship between language and culture in English textbooks published in Poland from the end of the 18th century to the middle of the 20th century and supplements knowledge about the local history of teaching English as a foreign language. The specific aim of the article is to illustrate changes in the way cultural issues are presented in English language teaching depending on the historical period. To achieve this objective, a qualitative analysis of the cultural content present in historical English textbooks was conducted. Its results were contrasted with three models of cultural education: national, intercultural and transcultural. The content analysis took into account textbooks passages referring to high and low culture in direct (texts and illustrations) and indirect ways (e.g. in grammar exercises). The analyses showed that the way cultural content is presented is derived from the teaching method used in the textbook, the needs of the learners, the institutional-ideological entanglements of language education and the changing state of theoretical knowledge on the role of culture in the glottodidactic process. The article demonstrates that the ability to shape knowledge about other nations, their cultures and representatives in the glottodidactic process was already being conducted in the past.